2021
DOI: 10.3390/ijerph182312475
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Productivity of Public Hospitals in Serbia Using DEA-Malmquist Model and Tobit Regression Model, 2015–2019

Abstract: Improving productivity within health systems using limited resources is a matter of great concern. The objectives of the paper were to evaluate the productivity, efficiency, and impact of environmental factors on efficiency in Serbian hospitals from 2015–2019. Data envelopment analysis, Malmquist index and Tobit regression were applied to hospital data from this period, and public hospitals in Serbia exhibited a great variation regarding their capacity and performance. Between five and eight hospitals ran effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…Therefore, it is reasonable and necessary to use the improved three-stage DEA method when measuring the efficiency of public hospitals for accurate results. The results for efficiency indicated that the mean efficiency score of public hospitals in Guangdong was 0.891, which was higher than that in Palestine (0.853) [ 32 ], Serbia (0.782) [ 45 ], Turkey (0.724) [ 69 ], Saudi Arabia (0.76) [ 50 ], Jordan (0.547) [ 70 ], and Iran (0.873) [ 71 ] and lower than that in Spain (1.016) [ 72 ], Wuhan, China (0.899) [ 73 ], and Taiwan, China (0.973) [ 74 ]. Only 38.1% of cities were found to be efficient in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is reasonable and necessary to use the improved three-stage DEA method when measuring the efficiency of public hospitals for accurate results. The results for efficiency indicated that the mean efficiency score of public hospitals in Guangdong was 0.891, which was higher than that in Palestine (0.853) [ 32 ], Serbia (0.782) [ 45 ], Turkey (0.724) [ 69 ], Saudi Arabia (0.76) [ 50 ], Jordan (0.547) [ 70 ], and Iran (0.873) [ 71 ] and lower than that in Spain (1.016) [ 72 ], Wuhan, China (0.899) [ 73 ], and Taiwan, China (0.973) [ 74 ]. Only 38.1% of cities were found to be efficient in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The number of healthcare institutions and beds were commonly chosen to represent capital investment [ 33 , 42 , 46 – 49 ]. Regarding labor variables, health workers [ 13 , 17 , 42 , 44 – 47 , 50 ], health technical workers [ 30 , 33 , 36 , 42 , 45 , 48 , 49 ], physicians [ 28 30 , 36 , 41 , 43 45 , 50 ], and nurses [ 17 , 28 , 30 , 36 , 41 , 42 , 44 , 45 ] were often regarded as types of labor investment. In the selection of output indicators, there are two main categories of expected and undesirable outputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DEA model measured relative efficiency by comparing and evaluating multi-input and multioutput DMUs, but it did not capture the key factors affecting efficiency. Thus, having calculated the efficiency score, we regressed environmental and managerial factors as the explanatory variables on the OTE to investigate the reasons for inefficiencies in medical institutions at various levels ( 41 ). In our study, we took into account the independence, availability, and comprehensiveness of data with the research focus.…”
Section: Methodsmentioning
confidence: 99%
“…DEA is a deterministic and non-parametric efficiency evaluation method proposed by Charnes et al [ 58 ]. Compared with the stochastic or parametric efficiency measurement method, DEA does not need to set the specific form of production function and does not contain random error [ 59 ]. The relative efficiency of DMUs is evaluated based on the degree of deviation from the frontier of DEA, and it shows strong objectivity.…”
Section: Methodsmentioning
confidence: 99%